2015
DOI: 10.1016/j.msea.2015.08.082
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of polycrystalline TRIP stainless steel micropillars

Abstract: The deformation mechanisms of the metastable austenite phase of a transformation induced plasticity (TRIP) stainless steel, AISI 301LN, have been investigated by compression of multicrystalline micropillars of different crystallographic orientations, with particular attention on the strain-induced phase transformation from austenite to martensite. Intergranular shearing and twinning were observed to be the primary deformation mechanisms, with a predominant <122> orientation developed in the austenitic phase, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…These results are in agreement with previous studies which demonstrate that, in austenitic grains deformed by cold working, the presence of microbands and twins provide not only strain hardening but also serve as nucleation sites to promote the formation of strain-induced martensite [33,34,35]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 …”
Section: -Results and Discussionsupporting
confidence: 93%
“…These results are in agreement with previous studies which demonstrate that, in austenitic grains deformed by cold working, the presence of microbands and twins provide not only strain hardening but also serve as nucleation sites to promote the formation of strain-induced martensite [33,34,35]. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 …”
Section: -Results and Discussionsupporting
confidence: 93%
“…Furthermore, as seen in Figure b, the flow stress is isotropic, with a constant value ranged between 1.1 and 1.3 GPa. The σ f values reported in Table are in agreement with those determined through the micropillar compressions tests on TRIP stainless steel …”
Section: Resultsmentioning
confidence: 91%
“…In this regard, at least two SF are required for the formation of a ϵ ‐band, with a respective unit displacement of around 0.1 nm depending on the certain slip system. Furthermore, recently, Roa et al found that the formation of ϵ ‐martensite is preferentially located in the regions near the grain boundary, where the material experienced complex stress fields, like higher shear stresses during compression. For those reasons, Δ h pop‐in reported in this study corresponds to the formation of around five to ten ϵ ‐platelets.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, ϵ ‐martensite may be considered as a dislocation pile‐up of SFs on every second {111} austenite plane, being the γϵ transformation a rather simple process. Recently, Roa et al observed the γϵ martensitic phase transformation in highly sheared austenitic zones, mainly located at the grain boundary.…”
Section: Introductionmentioning
confidence: 99%